The burden of cyberbullying on teachers - Singh, Nalini; Amin, Nyna; Devroop, Chatradari (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
This article explores the challenges teachers face in dealing with cyberbullying from the perspective of behavior management theory. We argue that dealing with cyberbullying places an additional burden on teachers. The research is based on narrative inquiry and focuses on the experiences of a participant named Amanda who works in a primary school. Amanda embodies the complexity of everyday life for teachers in a South African school. The analysis shows that teachers like Amanda are exposed to high levels of stress and burnout due to the administrative demands of dealing with bullying on social media, which distracts them from their actual pedagogical tasks. The inadequate institutional support has a negative impact on both their professional efficiency and their personal lives. The findings show that a holistic approach, including policy reforms, psychological support, and specialized training is needed to mitigate these effects.
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 7 (2) (2023)
Keywords: Behaviour management theory; Cyberbullying; Narrative enquiry; Social media; Teacher workload; Behaviour therapy for children; Cyberbullying; Teacher work groups; Mass media -- Social aspects; Behavior therapy for children